2003
DOI: 10.1111/j.0306-686x.2003.05624.x
|View full text |Cite
|
Sign up to set email alerts
|

Dividend Policy, Corporate Governance and the Managerial Entrenchment Hypothesis: An Empirical Analysis

Abstract: This paper analyses the agency explanation for the cross-sectional variation of corporate dividend policy in the UK by looking at the managerial entrenchment hypothesis drawn from the agency literature. Consistent with predictions, a significant U-shaped relationship between dividend payout ratios and insider ownership is observed for a large (exceeding 600 firms) sample of UK companies and two distinct periods. These results strongly suggest the possibility of managerial entrenchment when insider ownership re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
182
3
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(220 citation statements)
references
References 55 publications
27
182
3
8
Order By: Relevance
“…Some found family ownership and dividend payout to be positively related (Carney & Gedajlovic, 2002), while others found the relationship to be negative (Faccio, Lang, & Young, 2001;Farinha, 2003;Gugler, 2003;Setia-Atmaja, Tanewski, & Skully, 2009). Contrary to previous studies, we propose that family ownership influences dividend payouts in terms of different levels of cash flow rights of the controlling families, thereby creating a nonmonotonic relationship between those variables.…”
contrasting
confidence: 87%
“…Some found family ownership and dividend payout to be positively related (Carney & Gedajlovic, 2002), while others found the relationship to be negative (Faccio, Lang, & Young, 2001;Farinha, 2003;Gugler, 2003;Setia-Atmaja, Tanewski, & Skully, 2009). Contrary to previous studies, we propose that family ownership influences dividend payouts in terms of different levels of cash flow rights of the controlling families, thereby creating a nonmonotonic relationship between those variables.…”
contrasting
confidence: 87%
“…Crutchley and Hansen in their paper of dividend payout policy (1989) reached to similar results and they find that this policy along with financial leverage is one of the most powerful mechanisms in management control and financial decisions. Farinha (2003) also shows similar evidence in his study of British firms; he examined dividend policy and insider ownership as controlling factors. He found that agency problem increases when the insider ownership goes beyond a specific level, also this requires more dividend payment to minimize the agency problems.…”
Section: Literature Reviewsupporting
confidence: 60%
“…According to the corporate governance index provided by CLSA, Mitton (2004) found a remarkable positive correlation relationship between a company's governance structure and the cash dividend payment. After that, Farinha (2003), by using the data of the UK capital market and American capital market successively in 2003 and 2004, obtained a similar research conclusion. Contrary to that, the other view believing a negative correlation relationship between a company's governance mechanism and the cash dividend policy.…”
Section: Internal Control and Cash Dividend Policysupporting
confidence: 53%